The hidden messages in water - Emoto, Masaru, frey50 (Hillsboro, Ore. : Beyond Words Pub., 2004)
Dr. Emoto's work with water beautifully illustrates the healing power of love and gratitude. These building blocks of appreciation support our well-being in body, mind, heart and soul.
Keywords: Water: -- Philosophy; Water quality; Anthroposophy